Peran Organisasi Masyarakat Sipil Suar Asa Khatulistiwa dalam Pencegahan Kekerasan Seksual di Kota Pontianak - Silkania Swarizona; Sopian Lubis (Journal on Education, 2023)
Cases of sexual violence are still relatively high in Indonesia, even based on the Annual Records (Catahu) of the National Commission on Violence Against Women (KOMNAS Perempuan) for 2023, that there has been an increase in cases of sexual violence in Indonesia. However, since 2021, the Government has made a number of regulations to address this problem, one of which is Law Number 12 of 2022 concerning Crimes of Sexual Violence (TPKS Law). In the TPKS Law, it is explained that the active role of society is needed in overcoming the problem of sexual violence in Indonesia. By using a qualitative method, this study took the research object, namely the civil society organization Suar Asa Khatulistiwa (SAKA) to see the role of civil society in preventing sexual violence, especially in Pontianak City. The results of this study show that SAKA has played an active role in preventing sexual violence in Pontianak City. However, the Pontianak City Government still needs seriousness to be able to reduce the number of sexual violence in Pontianak City.